A Study on the factors affecting the police integrity: A case study at Ibu Pejabat Polis Kontinjen (IPK) Bukit Beruang, Melaka / Nazrul Amri Nazri and Norain Mohamad Hamdi - Nazri, Nazrul Amri; Mohamad Hamdi, Norain (Faculty of Administrative Science and Policy Studies, 2014)
The purpose of this research is to identify the factors affecting the police integrity at Ibu Pejabat Polis Kontinjen Bukit Beruang. This study is to examine the factors which affecting the integrity among the police at Ibu Pejabat Polis Kontinjen Bukit Beruang, Melaka and identifying the most significant factors which influencing the police integrity. The factors are comprises of the individual behavior, ethical leadership, and the organization factors. In order to achieve the objective of the study, the researcher used the convenient sampling as the sampling technique , through the questionnaire, and 150 police were chosen as the respondents and they are from various departments which are from the administration, traffic, narcotic, special branch, criminals, logistics and commercial. The data gathered has been analyzed by using various method and analysis including descriptive statistical analysis, reliability test, Spearman’s Bivariate Correlation, and Multiple Regression analysis. The result of correlation analysis revealed that all the three factors affect police integrity and the final results revealed, among the three (3) factors, the organization was found as the most significant factor that affect the police integrity.